A severe early presentation of cystic fibrosis in an infant with a homozygous c.1375_1383del CFTR variant- a case report - Yousef, Abdullah (Frontiers in Pediatrics, 2025)
BackgroundCystic fibrosis is a genetic disease affecting mainly the respiratory and digestive systems through CFTR gene mutations. The condition is characterized by the production of thick mucus, which can lead to severe respiratory complications and pancreatic insufficiency.We report a rare homozygous c.1375_1383del CFTR variant associated with early, clinically significant presentation. This highlights the importance of early recognition and genotype-specific management to maximize patient outcomes and improve quality of life.Case ReportWe present a 10-month-old female infant born to consanguineous parents with a significant medical history of chronic cough, cyanosis, failure to thrive, poor feeding, and irritability who ultimately required multiple hospitalizations for severe infections requiring mechanical ventilation and intravenous antibiotics. Initial evaluations included thorough clinical assessments and several diagnostic tests, including whole-exome sequencing, which revealed a homozygous c.1375_1383del variant in the CFTR gene. Aggressive therapy, including antipseudomonal antibiotics, was needed to clear the infection, in addition to administration of dornase alpha, 7% hypertonic saline, and pancreatic enzyme replacement therapy. These interventions contributed significantly to the gradual clinical improvement of the patient. At 18-month follow-up, the patient exhibited improved weight gain and a reduction in the frequency of exacerbations.ConclusionThe c.1375_1383del variant is a rare CFTR variant and is associated with early, clinically significant manifestations of cystic fibrosis in infants, which necessitates early recognition and aggressive management to improve patient outcomes. This case underscores the need for awareness of rare CFTR variants and their potential clinical implications, which can lead to tailored treatment approaches, ultimately enhancing the quality of life for affected individuals.